BUDAYA ORGANISASI DAN IMPLIKASINYA TERHADAP DISIPLIN KERJA KARYAWAN BAGIAN ADMINISTRASI PT. XYZ PEKANBARU - Risman, Risman (Komunitas Manajemen Kompetitif, 2023)
: The purpose of this research is to find out the effect that there is an organizational culture on the work discipline of the employees of the administration section of PT. XYZ Pekanbaru. Data was collected through questionnaires which were distributed to 38 respondents. By using quantitative analysis including validity and reliability tests, classical assumption tests, hypothesis testing through the t test and analysis of the coefficient of determination (R2). The t value is 6.553 and the t table is 2.208 and also the significance level is 0.000 <0.05, so the results of this research hypothesis mean that organizational culture has a clear impact on the work discipline of employees in the Administration Section. The relationship between organizational culture and the work discipline of employees in the administration section is positive, as evidenced by the result b of 0.883, which means that every one unit increase in the organizational culture variable will increase the work discipline of employees in the administration section of PT. XYZ .883 units. The value of the coefficient of determination (R Square) is 0.544, this means that organizational culture influences the work discipline of employees of the Administrative Section of PT XYZ Pekanbaru by 54.40 percent.